Lithobius (Ezembius) multispinipes n. sp., a new species of centipede from NorthWest China (Lithobiomorpha: Lithobiidae) - Pei, Sujian; Lu, Yanmin; Liu, Haipeng; Hou, Xiaojie; Ma, Huiqin; Zapparoli, Marzio (Zootaxa, 2016)
The centipede subgenus Lithobius (Ezembius) Chamberlin, 1919 comprises a group of about 60 species known from the Near East across Siberia and Central Asia to China, and Japan, and Southwards into the Northern Indian subcontinent and the Northern part of the Oriental region (Eason 1992, Zapparoli 1999). It is also known from Alaska in Western North America (Zapparoli & Edgecombe 2011). Although the subgenus was formally proposed as new and described in 1923 (Chamberlin 1923), according to Jeekel (2005) its name had been already validated in 1919 (Chamberlin 1919). Ezembius is characterized by the presence of 2+2 or 3+3 coxosternal teeth, antennal articles fixed at 20 or thereabouts, tergites generally without posterior triangular projections and tarsal articulation of legs 1–13 distinct (Chamberlin 1923, Zapparoli & Edgecombe 2011).